The Small Bang - (:unkn) unknown (My University, 2022)
The Small Bang represents a recently begun ERC-funded project dedicated to discovering the origins of the Bangime language and Bangande people. The language and its speakers are of particular interest to West African research as Bangime is one of the only isolates spoken in the region and the ancestors of the Bangande are also unknown. Using the latest computer-assisted technologies, the Bang team is amassing linguistic and genetic data and comparing them with a hitherto unexplored set of languages and peoples in search of a hidden history. Preliminary hypotheses suggest geographic isolation that has led to a bottleneck of at least 9,000 years. The question as to from whom the people and their language originated remains open.
Keywords: African Research